Enhancing the productivity performance of Cyprinus carpio L. by Manihot utilissima Pohl. leaves supplementation - Teuku Reza Efianda; Uci Elfana Sari; Humeira Humeira; Kiki Rishki Ananda (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Cyprinus carpio is an economically crucial freshwater commodity in Indonesia and across the globe. Fish demand has a rising trend, which not in line with productivity. Innovation and aspects of food safety are the primary keys to increasing productive capacity. Therefore, the utilization of Manihot utilissima leaves as an alternative to improve national fish's productivity rate is a worthy consideration. They have multiple nutrients, including protein and fat needed by C. carpio seeds. This study aims to determine the optimal dose of M. utilissima supplementation to increase the productivity of C. carpio seeds. The methodology consisted of four treatments (0.5 mL/250 g, 10 mL/250 g, 15 mL/250 g) with four replications for 21 days. The outcome showed that P4 treatment (15 mL) could increase the relative growth rate by 21.10%/day, and it decreased the feed conversion ratio by 0.84. However, there is no significant effect on the survival rate. The study concludes that P4 treatment (15 mL) has positively increased the relative growth rate of C. carpio, and decreased its feed conversion ratio.